THE REVOLUTIONARY FINTECH WAVE: THE IMPACT AND POTENTIAL OF FINANCIAL SERVICES - Sanagasetty Satyavani; A Suryanarayana (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Financial services are undergoing disruption at a breakneck pace led by the rapid emergence of FinTech. This article aims to assess the impact and potential of FinTech innovations by examining how they disrupt incumbent financial systems and generate new possibilities for service providers as well as consumers. It aims to offer a sound, overall conceptual framework explaining FinTech’s contribution in transforming the financial environment, highlighting underlying trends, technologies and business models that drive this revolution. The construction of the present manuscript is exploratory in nature and provides an overview of some important domains related to FinTech, like blockchain, digital banking, peer-to-peer lending and robo-advisory services. By combining academic and industry viewpoints, it reveals the most relevant areas of opportunity as well as considerable challenges resulting from FinTech disruption. Results include greater visibility into how FinTech is increasing financial inclusion, driving down the cost of transactions and how FinTech continues to make a more personalised financial marketplace possible. The contributions of this article are as follows: (i) critical examination of the integration of FinTech into broader financial systems, including an updated assessment of the innovation process, regulatory practices adopted and future pipeline directions; and (ii) new dimensions in understanding FinTech, its growth and challenges. The potential implications for policymakers, incumbents, and entrants, however, are profound, as there are new paths to growth and investment and collaboration in a digital world. Although the article provides an in-depth analysis, as the FinTech is fast-moving, there could be unforeseen application issues or opportunities that are not covered by this analysis, becoming a limitation. Nonetheless, its originality lies in filling a void by incorporating other levels and ages of the FinTech revolution, which allows for an estimation of trends for the future development of the marketisation of financial services.